Aulonemia insolita (Bambusoideae: Bambuseae: Arthrostylidiinae) a new remarkable woody bamboo species with internode dimorphism endemic to Bolivia and Peru - Jiménez-Pérez, Ivan; Reátegui Natalia; Malpartida-Garay, Celia Fiorella; Ruiz-Sanchez, Eduardo (Phytotaxa, 2025)
Species belonging to the genus Aulonemia have distribution across Mexico, Central America, northern and central Andes, the Guiana shield and southern Brazil. Three Aulonemia species: Aulonemia hirtula, A. queko, and A. herzogiana are known to have dimorphic internodes. In this study, we describe a new species of Aulonemia, characterized by culms with a pattern of one long internode followed by four to five shorter internodes. Notably, this species exhibits erect culm leaf blades, an uncommon trait within the genus. This study provides a comprehensive description of this new Aulonemia species, along with a distribution map, photographs and a morphological key to the species of Aulonemia with dimorphic internodes.